Structure of the signal recognition particle by electron microscopy. - Andrews, D W (1985)
The signal recognition particle (SRP) is a ribonucleoprotein consisting of six distinct polypeptide components and one molecule of small cytoplasmic RNA (7SL RNA). The particle was previously shown to function in protein translocation across and protein integration into the endoplasmic reticulum membrane. Homogeneous signal recognition particle preparations were visualized by electron microscopy (i) after negative staining, (ii) by dark-field imaging of unstained specimens, and (iii) by platinum-shadowing. The results of each of these different techniques indicate that the signal recognition particle is a rod-shaped particle 5-6 nm wide and 23-24 nm long.